Corporate social responsibility and corporate misconduct - Ferrés, Daniel; Marcet, Francisco (Journal of Banking & Finance, 2021)
We analyze whether price fixing firms modify their Corporate Social Responsibility (CSR) activities around the revelation of the corporate misconduct. Our paper is the first empirical study to specifically explore the timing and the stability of the new CSR investments in firms involved in corporate misconduct. Our results show that firms that participate in illegal price fixing schemes increase their CSR initiatives around the time when they become the target of an antitrust investigation - not before. Moreover, the new CSR initiatives are mainly concentrated on improving positive CSR rather than in reducing further CSR concerns. Finally, we show that the new CSR efforts are not only associated with lower fines. We find that colluding firms tend to lose sales following a cartel breakup, although the decline in sales is less pronounced for those cartel firms that take anticipatory CSR actions to limit the negative impact of fraud revelation.